2015
DOI: 10.1016/j.ejca.2015.08.027
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age on health-related quality of life in cancer populations: A pooled analysis of randomized controlled trials using the European Organisation for Research and Treatment of Cancer (EORTC) QLQ-C30 involving 6024 cancer patients

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
74
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(95 citation statements)
references
References 39 publications
14
74
6
1
Order By: Relevance
“…Furthermore, they scored significantly better than the elderly on interest in sex. 21 A likely explanation for the differences in HR-QOL between younger and older survivors is the fact that, in the natural course of aging, a decline in functional status, and, thus, physical HR-QOL occurs. 10 That study found that adolescents and young adult thyroid cancer survivors (17-39 years) reported significantly less neuromuscular, voice, sympathetic, and throat/mouth complaints than older (40 years) survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they scored significantly better than the elderly on interest in sex. 21 A likely explanation for the differences in HR-QOL between younger and older survivors is the fact that, in the natural course of aging, a decline in functional status, and, thus, physical HR-QOL occurs. 10 That study found that adolescents and young adult thyroid cancer survivors (17-39 years) reported significantly less neuromuscular, voice, sympathetic, and throat/mouth complaints than older (40 years) survivors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, patients with similar disease states but with different demographics (eg, age, gender, socioeconomic status etc.) may report different scores when assessed with HRQoL tools . Aside from demographics, cultural background also impacts patients’ experience of their disease and treatment and thus will affect the scores reported via HRQoL tools .…”
Section: Patients’ Experience With Hcv Infectionmentioning
confidence: 99%
“…3 Patient reported outcome measures (PROM) are an established component of cancer outcomes reporting. 6 In a critical review, Aggarwal et al summarized global radiation therapy research between 2001 and 2015, and reported increasing numbers of HRQOL papers from a range of different countries. Health-related quality of life (HRQOL) assessment is embedded in many clinical trials.…”
Section: Introductionmentioning
confidence: 99%